4-Nonylphenol degradation changes microbial community of scale-up Anaerobic Fluidized Bed Reactor. (1st August 2020) - Dornelles, Henrique de Souza; Motteran, Fabrício; Sakamoto, Isabel Kimiko; Silva, Edson Luiz; Varesche, Maria Bernadete Amâncio
Abstract: Nonylphenol Ethoxylate (NPe) is a nonionic surfactant widely applied in domestic and industrial uses and its degradation generates the endocrine disruptor 4-Nonylphenol (4-NP). The effects of this compound in biological sewage treatment are uncertain, especially in anaerobic systems. The aim of this study was to assess the 4-NP removal and degradation in scale-up (20 L) Anaerobic Fluidized Bed Reactor (AFBR) filled with sand as support material, operated with Hydraulic Retention Time (HRT) of 18 h, fed with synthetic sewage plus 4-NP, performed in four phases named Phase I (894 mg COD L −1 ), Phase II (878 mg COD L −1, 127 μg 4-NP L −1 ), Phase III (940 mg COD L −1, 270 μg 4-NP L −1 ) and Phase IV (568 mg COD L −1, 376 μg 4-NP L −1 ). 4-NP did not affect reactor stability and organic matter removal remained stable at 94%. Highest 4-NP removal (78%) occurred for highest 4-NP influent (Phase IV), which resulted from biomass adaptation in the presence of ethanol. Through the 4-NP total mass balance, about 70% was biodegraded and 1% adsorbed on the sand bed. 4-NP addition promoted selection of microbial consortium strongly linked to aromatic compounds and surfactants degradation such as Geothrix, Holophaga, Aeromonas, Pelobacter, Pseudomonas, Delftia . Graphical abstract: Image 1 Highlights: 4-NP increased abundance of genera related to aromatic compounds degradation. 4-NP addition and load increase did not affect AFBR performance and stability. Microbial community stratification occurred after 4-NP addition. Geothrix was the most abundant genus after 175 days with 4-NP. Relative abundance of Methanosaeta increased in sand bed after 4-NP addition.